Has the commercialisation of medical research gone too far? - Barker, Ian R. (International Journal of Research in Medical Sciences, 2017)
Government policy has been complicit in the increasing role of commercial companies in research, which in turn have little incentive to share the benefits of research. As a result, huge swathes of medical research rely on commercialisation and related patent protection in order to thrive. There is a distinct lack of evidence that commercialisation has led to an improvement in public health, the claim of increased innovation simply does not have empirical support. Commercialisation has led to skewed benefits in favour of companies, whereby industry is using the public’s resource without adequately paying for it, this imbalance may be seen as a form of exploitation. In this paper I argue that the skewed relationship between commercial and public interest needs to be addressed in order to ensure we meet healthcare needs of our patients in the future and ensuring the healthcare remains affordable.